تنفيذ الطريقة الإلقائية في درس الإملاء - Rizqiyah, Wakhidatur (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
Santriwati's ability to listen the lesson is influenced and dependent on the clarity and truth of the pronunciation of the Master or the reader of the Imla '. With the Ilqo'iyah Method the teacher can expose the knowledge in a sequential phrase then connect it in a sequential and controlled manner by a good and interesting technique. The purpose of this study is to find out what the Imla teachers 'efforts in applying Ilqo'iyah Methods in Imla Learning', and to know the benefits and effects of Imla 'lessons. This study is a field study, and to achieve the above objectives, the researcher uses, observation method, interview method and documentation method. The analysis technique used is technique from Miles and Huberman, that is by reducing data, then present data, then draw conclusion and verification. It is noteworthy that the application of the Ilqoiyah method in Imla 'lessons has been applied during the reading of the Imus' lecture with the lecture method, and the justification of the writing on the chalkboard with the explanation, before, a brief exposition of the subject matter using the method of description, lastly, the teacher's story relating to the material , delivered by the method of telling stories.  Keywords: Implements, Imla Lessons', several attempts, descriptions, exercises